Comparison Of Two Hybrid Algorithms On Incorporated Aircraft Routing And Crew Pairing Problems - Mohamed N. F.; Mohamed N. A.; Mohamed N. H.; Subani N (Institute of Advanced Engineering and Science (IAES), 2024)
Indexed by Scopus